2019
DOI: 10.1108/jcom-07-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

A reliable and valid measurement scale for assessing internal crisis communication

Abstract: Purpose There appears to be a growing concern over the lack of scales for measuring internal crisis communication (ICC) in the course of an organizational crisis. Noting this compelling evidence, an analysis of results from earlier exploratory studies demonstrated a strong need for a sound scale with adequate psychometric properties. On that account, the purpose of this paper is to develop a valid scale for ICC. Design/methodology/approach This study examined the conceptualization and operationalization of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…In line with previous research (e.g. Adamu and Mohamad, 2019), the present study found that high-quality internal crisis communication increases EOR. More specifically, the findings imply that the quality of communication in times of crisis can enhance employers' perceived trustworthiness and improve employees' commitment and job satisfaction.…”
Section: Perceptions Of Internal Communicationsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous research (e.g. Adamu and Mohamad, 2019), the present study found that high-quality internal crisis communication increases EOR. More specifically, the findings imply that the quality of communication in times of crisis can enhance employers' perceived trustworthiness and improve employees' commitment and job satisfaction.…”
Section: Perceptions Of Internal Communicationsupporting
confidence: 93%
“…(2) The study once again empirically demonstrated the advantages of high-quality internal communication for EOR (e.g. Adamu and Mohamad, 2019). We also clarified that the perceived quality of internal communication is a fruitful predictor of employees' attitudes toward their employer, which highlights the importance of internal communication for organizations.…”
Section: Conclusion Implicationsmentioning
confidence: 56%
See 1 more Smart Citation
“…Frandsen and Johansen, 2011), there has been a rise of research studies on internal crisis communication in the past decade, all of which points to the importance of distinguishing employees from other stakeholders in crisis communication due to their different information roles and needs (e.g. Frandsen and Johansen, 2011;Adamu and Mohamad, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal crisis communication is critical in creating shared crisis awareness in organizations and to prevent misalignment between employee and organizational understandings and behaviors toward the crisis situations (Jin et al, 2018;Kim, 2018). Employees should be involved in the communication and actions of the organizations because they can and should be major actors in developing a culture of early problem detection and to help organizations better handle the crises (Adamu and Mohamad, 2019). Crises are also a time of transformation during which JCOM 25,3 organizational actions and employee reactions can create and transform organizational culture (Strandberg and Vigsø, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%